Post-soul Black cinema : discontinuities, innovations, and breakpoints, 1970-1995 - Grant, W. R., 1967- (Studies in African American history and culture., 2004)
Post-Soul Black Cinema traces the movement of African American filmmakers and images, as they move from the margins to the mainstream of American cinema.